Effects of Rhodotorula mucilaginosa on the Immune Function and Gut Microbiota of Mice - Ge, Ye; Huang, Kaisen; Xie, Weitian; Xu, Chunhou; Yao, Qiucheng; Liu, Ying (Frontiers in Fungal Biology, 2021)
As a dominant species among marine yeasts, Rhodotorula benthica accounts for ~50% of all marine yeasts. Rhodotorula is rich in a variety of bioactive substances and commonly used in the production of carotenoids by microbial fermentation and is worth developing. Therefore, the present study used a strain of Rhodotorula mucilaginosa isolated from the coastal waters of the South China Sea as the target yeast to investigate its impact on the immune function and gut microbiota of mice. A total of 200 mice were randomly divided into gavage groups and control group and garaged for 30 consecutive days at different concentration. Samples were collected on day 15 and day 30 of gavage administration. The results showed that R. mucilaginosa ZTHY2 could increase the thymus and spleen indices of mice, and its effect on the thymus index was more significant after long-term gavage administration. Short-term (15 days) gavage administration of R. mucilaginosa suspension enhanced delayed hypersensitivity in mice, increased serum IgG, IgA, and IL-2. Long-term (30 days) gavage administration of R. mucilaginosa suspension significantly enhanced the phagocytosis of macrophages in mice and significantly increased serum TNF-α and INF-γ. R. mucilaginosa ZTHY2 altered the structure of the gut microbiota of mice at the phylum and genus levels, leading to an increased relative abundance of Firmicutes and Lactobacillus and a decreased relative abundance of Bacteroidetes. This strain increased the beneficial intestinal bacteria and reduced the harmful intestinal bacteria in mice. This study provides experimental evidence and lays the foundation for the future development and application of this strain as a microecological source of carotenoids.